Programa educativo y conocimiento en medidas de prevención sobre la enfermedad renal crónica en adulto mayor - Cardenas Chavez, Gladys Lucy (2016)
This investigation of type - quasi-experimental design of linear calibration pre - post test was performed on older adults with chronic users Polyclinic Victor Larco Herrera - Essalud Trujillo between October 2014 and May 2015, in order to determine the effectiveness of the educational program "Caring for my kidney" in the level of knowledge of preventive measures for chronic kidney disease in the elderly. The sample universe consisted of 40 people who met the inclusion criteria. The data were obtained by applying the Survey of Knowledge, Attitudes and Practices Health and Renal Disease before and after performing educational program "Caring for my kidney", taking into account the relevant ethical considerations. The results were presented in tables and graphs determining the level of statistical significance with the student's t test, with the results: 1) The level of knowledge in the pretest is low in 92.5% of the elderly and a half only 7.5% of adults, while after participating in the educational program only 5.0% of adults have level through knowledge and the remaining 95.0% level of knowledge it is high; 2) The educational program "Caring for my kidney" was effective because the difference is statistically significant given that the value of p is less than 0.05.